AB0067 Association of CXCL10 AND CXCL13 in Active Adult Onset Still's Disease: Expression in Serum and Skin, and Disease Activity. (9th June 2015) - Kim, H.-A.; Han, J.H.; Suh, C.-H.; Jung, J.-Y.
Abstract : Background: CXCL10 is produced in response to interferon-γ, and tumor necrosis factor-α triggers the accumulation of activated lymphocytes via interaction with a specific receptor, CXCR3, creating an amplification feedback loop. CXCL13 is constitutively expressed in secondary lymphoid tissues, and the expression is upregulated by TNF-α, via T cell stimulation, and CXCR3 and CXCR5 are known to serve as receptors for CXCL13. Objectives: It appears that CXCL10 and CXCL13 could play a potential role in the pathogenesis of adult onset Still's disease (AOSD), therefore, we investigated the associations between CXCL10 and CXCL13 levels and clinical manifestations in patients with active AOSD. Methods: Blood samples were collected from 39 active AOSD patients and 40 healthy controls (HC). Of the AOSD patients, follow-up samples were collected from 15 9.6±9.2 months later. CXCL10, CXCL13, and CXCR3 expression levels in biopsy specimens obtained from 26 AOSD patients with skin rashes were investigated via immunohistochemistry. Results: The CXCL10 level of AOSD patients (1, 031.3±2, 019.62 pg/mL) was higher than that of HC (104.35±47.92 pg/mL, p=0.006). Also, the CXCL13 level of AOSD patients (158.8±151.2 pg/mL) was higher than that of HC (23.5±18.1 pg/mL, p<0.001). Serum CXCL10 levels correlated with ferritin and aspartate transaminase levels, and systemic scores. Serum CXCL13 levels correlated with those of hemoglobin, C-reactive protein, ferritin, and albumin, and systemic scores. Also, serum CXCL10 levels correlated with those of CXCL13. In follow-up AOSD patients, the levels of CXCL10 and CXCL13 fell significantly (p=0.002 and p=0.001, respectively). On immunohistochemistry, the percentages of inflammatory cells expressing CXCL10 ranged from 0 to 85% (mean, 25.77±23.28%), CXCL13 from 1 to 72% (mean, 23.27±22.17%), and CXCR3 from 2 to 65% (mean, 16.35±18.54%). The percentage of CXCL10-positive inflammatory cells was higher in skin biopsy samples exhibiting mucin deposition than in those that did not (p=0.01). CXCL13 levels were correlated with those of CD4 (r=0.453, p=0.02) and CD68 (r=0.464, p=0.017). Conclusions: Serum CXCL10 and CXCL13 levels may serve as clinical markers for assessment of disease activity in AOSD. CXCL10/CXCR3 and CXCL13 may contribute to the inflammatory response, especially skin manifestations in AOSD. References: Manzo A, Vitolo B, Humby F, et al. Mature antigen-experienced T helper cells synthesize and secrete the B cell chemoattractant CXCL13 in the inflammatory environment of the rheumatoid joint. Arthritis Rheum 2008;58:3377-3387. Kasama T, Furuya H, Yanai R, et al. Correlation of serum CX3CL1 level with disease activity in adult-onset Still's disease and significant involvement in hemophagocytic syndrome. Clin Rheumatol 2012;31:853-860. Laragione T, Brenner M, Sherry B, et al. CXCL10 and its receptor CXCR3 regulate synovial fibroblast invasion in rheumatoid arthritis. Arthritis Rheum 2011;63:3274-3283. Disclosure of Interest: None declared